Indoleamine-2,3-Dioxygenase 1 Deficiency Suppresses Seizures in Epilepsy - Deng, Ning; Hu, Jiao; Hong, Yu; Ding, Yuewen; Xiong, Yifan; Wu, Zhiyong; Xie, Wei (Frontiers in Cellular Neuroscience, 2021)
Background: Indoleamine-2,3-dioxygenase 1 (IDO1) is the initial and rate-limiting enzyme in the metabolism of tryptophan (TRP) to kynurenine (KYN). IDO1-dependent neurotoxic KYN metabolism plays a crucial role in the pathogenesis of many neurodegenerative disorders. However, the function of IDO1 in epilepsy is still unclear. Objective: In this study, we investigated whether IDO1 deficiency could affect epilepsy in a lithium-pilocarpine-induced model. Methods: Patients with epilepsy and controls were enrolled. Male C57BL/6 mice and IDO1 knockout (KO, IDO1-/-) mice were subjected to intraperitoneal injection of lithium and pilocarpine to induce epilepsy. The levels of IDO1 and concentrations of TRP and KYN in patients with epilepsy and epileptic mice were evaluated by enzyme-linked immunosorbent assay (ELISA) and liquid chromatography-mass spectrometry (LC-MS), respectively. Then, behavioral phenotypes related to epileptic seizures and neuronal damage were compared between KO and wild-type (WT) mice with lithium-pilocarpine-induced epilepsy. To explore the underlying pathways involved in the effects of IDO1 deficiency, the concentrations of kynurenic acid (KYNA) and quinolinic acid (QUIN), glial cell activation, the levels of major pro-inflammatory cytokines, and antioxidant enzyme activity were measured by LC-MS, immunohistochemistry and ELISA. Results: In this study, IDO1 levels and the KYN/TRP ratio in the serum and cerebrospinal fluid (CSF) were increased in patients with epilepsy. In addition, IDO1 levels, the KYN/TRP ratio and the levels of pro-inflammatory cytokines in the serum and hippocampus were increased in mice during the acute phase and chronic phase after status epilepticus (SE). Furthermore, IDO1 was localized in microglial cells in epileptic mice. IDO1 deficiency delayed SE onset and attenuated the frequency, duration and severity of spontaneous recurrent seizures (SRSs). Moreover, IDO1 deficiency improved neuronal survival. Additionally, IDO1-/- epileptic mice showed progressive declines in QUIN production, glial cell activation and pro-inflammatory cytokines levels, and enhanced antioxidant enzyme activity. Conclusions: IDO1 deletion suppressed seizures and alleviated neuronal damage through reducing the IDO1-dependent production of neurotoxic metabolites, which finally inhibited glial cell activation and pro-inflammatory cytokine production and improved antioxidant enzyme activity. Our study demonstrates that IDO1 may be involved in the pathogenesis of epilepsy and has the potential to be a therapeutic target for epilepsy treatment.